Personal Identity and Narrativity - García Serrano, Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
How can we have a satisfactory explanation of the primary subjectivity of human consciousness, taking into consideration our relations to other people and to the natural world? The essay that follows discusses different facets of the narrative nature of personal identity, defending a new version of the concept of a synthetic unity of apperception. Although the author’s account disagrees with an essential point of Kantian philosophy’s hermeneutical critique of subjectivism, the account is designed to be compatible with other aspects of this critique.